Textural Properties Of Glutinous Rice Flour Gels And Dodol As Influenced By High Diastase Honey - Seow, Eng Keng (2019)
Dodol is a chewy, starchy and sweet confection commonly served during festivals in Malaysia. Texture deterioration of dodol is often associated to the hardening process caused by retrogradation of starch. Present study aimed to investigate the feasibility of using high diastase raw bee honey to reduce hardening of dodol during storage and compare the acceptance of honey-added dodol. A range of glutinous rice flour (GRF) gels or dodol incorporated with honey were prepared. Conventional GRF (congel), honey bee honey-GRF (honeygel), kelulul bee honey-Glcf (kelugel), heated honey bee honey-GRF (heated honeygel), heated kelulut bee honey-GRF (healed kelugel), and sugar-GRF gels were assessed for viscosity, rheological and hardness parameters. Compared to other gels, only honeygel showed appreciable drop in viscosity when the gels were maintained at 55 oe for 30 min and significantly (p<0.05) lowest hardness value (0.64 N) during storage for 7 days. Honeygel was significantly (p<0.05) less elastic (more liquid-like) with the lowest O' (elastic modulus) value, as compared to congel and kelugel. There was a 5.37% decrease in O' value from 6.33 to 5.99 Pa after 30 min of testing. This behaviour was thought to be due mainly to the relatively high diastase content ofthe raw bee honey. Similar experiments were repeated in dodol. Conventional dodol (condol), honey bee honey-dodoI (honeydol) and kelulut bee honey-dodol (keludol) were assessed for texture profile (hardness, adhesiveness, springiness, cohesiveness, gumminess, resilience), multiple extrusion (Winf, WI, ni), stress relaxation (Fmax, kr, kz) and thermal analysis (Tonset, Tpeak,